Is green industrial policy the right choice for the EU? - Christian Sandström; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2025)
This paper critically evaluates the European Union's shift towards large-scale green industrial policies. It highlights the risks of government-directed resource allocation, such as inefficiencies, misaligned incentives, rent-seeking, and lobbying. Politicians and bureaucrats at the EU level lack the ability to identify the future industries, products, and technologies for this policy to work effectively. The EU is not designed to operate large top-down interventions successfully. There is a substantial risk that large amounts of resources will be spent on initiatives that ultimately fail. Instead, this paper emphasizes competition- and technological-neutral frameworks, emissions trading systems, and general policy incentives. The paper concludes that a decentralized, market-driven approach is more sustainable for fostering innovation.
Keywords: H50; L52; O38; P16; 330; New industrial policy; green investments; Innovation policy; Missionoriented policies